Impact of cluster front line demonstration on mustard productivity in Lalitpur district of Uttar Pradesh - NK Yadav; Nitin Kumar Pandey; Dinesh Tiwari; Shalini; SPS Somwanshi (Journal of Oilseed Brassica, 2025)
Mustard [Brassica juncea (L.) Czern & Coss] is one of the most important oilseed crop of  Bundelkhand region of Uttar Pradesh, India. KrishiVigyan Kendra, Lalitpurconducted 135 Cluster Front Line Demonstrations (CFLDs) on mustard during Rabi season of 2019-20 to 2020-21. The front line demonstration (FLD) is one of the most powerful tools for transfer of technology. The critical inputs were identified in existing production technology through meetings and discussion with farmers. Prevailing farmers practices were treated as control for comparison with recommended practices. An average yield of mustard were 14.7 q/ha and 15.3 q/ha during 2019-20 and 2020-21, respectively under demonstrated technology however under farmers practices the average yield were 12.0 q/ha and 11.2 q/ha during respective years and the average yield of two year was reported 15.0 q/ha over farmers practices (11.6 q/ha). On the basis of average of two years, net returns from CFLD practices were Rs 38816/ha as compared to Rs 25533/ha in farmers practices. An average BCR were 2.95 in recommended practices as compared to 2.4 in farmer’s practices.